Dialog z Vzhodom v uprizoritvah Jerneja Lorencija - Rošker, Anja (Amfiteater (Ljubljana), 2017)
This article discusses the performances directed by Jernej Lorenci between 2005 and 2011, in which he explores various modes of portraying archetypal conception in intercultural performances in dialogue with the East. The period of such dialogue with the East begins with the 2005 staging of the Tibetan mystery play Tchrimekundan or The Unblinded . Despite the depurated stage images, the play is materialised with a touch of the Buddhist tradition and thus consents to Jung's thesis of the cultural imbuement of archetypal images. The 2005 staging of the Slovenian dramatisation of the Mesopotamian epic poem Epic of Gilgamesh uses signs having a symbolic meaning that is recognised and spread throughout the East as well as the West, thus functioning as a means of surpassing cultural differences and thereby approaching the common archetypal cores. In the performance of Japanese Noh plays collected under the title Wind in the Pines, the director once again chooses a different path and substitutes certain elements of Eastern performance art traditions with local archetypal conceptions. Lorenci's creative phase of dialogues with the East ends with the staging of a European adaptation of the Sufi epic poem The Conference of the Birds. Since it operates with signs from the banal everyday life, the performance seemingly distances itself from the content of the collective unconscious. Nevertheless, it captures the essence of Islamic mysticism precisely in the absence of the sacral. The analysis of the culturally imbued signs of the discussed performances is based on the continuum of intercultural connection, conceived by Helen Gilbert and Jacqueline Lo, and on the seven-step model by Marvin Carlson, which established possible relations between cultures within a performance. The article comes to the conclusion that through dialogue with the East, Jernej Lorenci has formed a distinct directing style, which emphasises the cultural diversity of archetypal conceptions, thus continually traversing between the collaborative and imperialistic pole of the continuum of intercultural connection.
Keywords: archetype; colonialism; Črimekundan ali Brezmadežni; Ep o Gilgamešu; Epic of Gilgamesh; gledališke uprizoritve; gledališki režiserji; interculturalism; kolonializem; Lorenci, Jernej, 1973-; medkulturnost; Tchrimekundan or The unblinded; The conference of the birds; Veter v vejah borov; Wind in the pines; Zborovanje ptic